A decision-making learning and assessment tool in laparoscopic cholecystectomy. - Sarker, S; Rehman, S; Ladwa, M; Chang, A; Vincent, C (2009)
AIMS: Making correct decisions is an integral part of surgical competency and excellence. The learning of this expert skill takes years to accumulate during training. To date there has not been an attempt to accelerate this learning process by developing a tool. In our present study we develop a self-appraisal computer software learning and assessment decision-making tool for laparoscopic surgery. It aims to accumulate several years of varied surgical experience, so the trainee can start to learn the complexities of surgical decision making in various types of cases. In this study we aim to validate the tool. METHODS: Three decision-making modules were developed in a computer program for laparoscopic cholecystectomy: knowledge of operation, operative surgical technique and operative task completion. The latter two modules were based on answering questions based on watching recorded live operations from a library of 100 recorded laparoscopic cholecystectomies of various grades. The questions were devised by two experienced surgeons with more than 14 years postgraduate surgical experience. To validate the tool two groups with varying surgical experience were assessed: intermediate and expert surgeons. These groups were determined by the number of laparoscopic cholecystectomies performed as well as of number of years of operative surgical experience. RESULTS: A total of 20 subjects were assessed, 12 intermediate and 8 experts surgeons. Mean time to perform the programme was 21 min (range 18-45 min). Using the Mann-Whitney test, p < 0.05, construct validity was demonstrated in the surgical technique and completion of task modules as well as the total combined scores. CONCLUSIONS: Our computer-based decision-making learning tool for laparoscopic cholecystectomy seems to have face, content, concurrent and construct validities. Surgical decision making is a multifaceted process; by assessing how and why decisions are made effectively, focussed surgical training may be achieved. We aim in the future to determine if the self-appraisal decision-making tool improves or accelerates surgical training.